2008
DOI: 10.2320/matertrans.mc200768
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar Welding of Al and Mg Alloys by FSW

Abstract: Microstructures and mechanical properties of dissimilar welding joint between Al alloy and Mg alloy by Friction Stir Welding (FSW) were investigated in comparison with laser welding of the same combination. Dissimilar joint of Al and Mg alloy by laser welding was very brittle because of building up Mg 17 Al 12 inter metallic compounds in fusion zone. On the other hand, FSW is anticipated to welding dissimilar alloys with enough joint strength because it is a solid-state process without melting. In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 18 publications
0
40
0
3
Order By: Relevance
“…The previous researches have reported that fracture of FSWed specimens occurred near intermetallic compounds such as Al 12 Mg 17 and Al 3 Mg 2 which were formed in the SZ during dissimilar FSW. 18,22) Hence, it is believed that formation and/or distribution of the intermetallic compounds should be controlled for further improvement of the mechanical properties by various processing parameters. Figure 10 shows the surface appearances of the TWBs produced at the tool traverse speeds of (a) 100 and (b) 500 mm/min under the constant tool rotation speed of 1400 rpm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous researches have reported that fracture of FSWed specimens occurred near intermetallic compounds such as Al 12 Mg 17 and Al 3 Mg 2 which were formed in the SZ during dissimilar FSW. 18,22) Hence, it is believed that formation and/or distribution of the intermetallic compounds should be controlled for further improvement of the mechanical properties by various processing parameters. Figure 10 shows the surface appearances of the TWBs produced at the tool traverse speeds of (a) 100 and (b) 500 mm/min under the constant tool rotation speed of 1400 rpm.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] However, there were not a lot of researches on dissimilar FSW between the aluminum and magnesium alloys. [18][19][20][21][22] Hirano et al 18) have carried out a dissimilar FSW between 1050 aluminum and AZ31 magnesium alloys, and reported that an intermediate layer was formed near their bonded interface, which was composed of an intermetallic compound Al 12 Mg 17 and an undefined compound. Sato et al 19) also have studied on the same system as Hirano et al, 18) although the plate thickness was different.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these difficulties, one needs to choose the appropriate welding parameters such as positioning of the materials, tool rotation rate, tool traverse speed and position of the tool from weld interface. In this section, we will discuss about Friction Stir Welding of AZ31B Magnesium Alloys and AA5052 Aluminium alloys [7]. The materials used for butt joints were extruded AZ31B magnesium alloy and A5052-H aluminum alloy plate.…”
Section: Friction Stir Welding Of Different Alloys Having Dissimilmentioning
confidence: 99%
“…Recently, the degree to which FSW can join dissimilar metals had been investigated in the combinations of Mg/Al [2][3][4][5] , Al/Ti 6) and Mg/Ti [7][8][9] . Among them, Mg/Ti dissimilar joining by FSW was investigated between Mg-Al-Zn alloy and commercial pure titanium.…”
Section: Introductionmentioning
confidence: 99%